Symbolic Interaction as a Communication Strategy to Increase the Competitiveness of Job Applicants in the Context of Corporate Communication - Riandia Paramitha, Ni Ajeng; Noer , Mochammad Kresna (CV. Publikasi Indonesia, 2025)
Corporate communication plays a vital role in shaping organizational image and attracting talent, with digital platforms increasingly used in recruitment. Curriculum Vitae (CVs) and portfolios serve as crucial communication tools reflecting professional identity, yet CVs often fail to convey personality or in-depth expertise. This study aims to analyze how the integration of CVs and portfolios can increase applicant competitiveness in job selection by examining the perceptions of users (employers) and HR, through the lens of Goffman's Symbolic Communication Theory and DeVito's Interpersonal Communication Theory. Employing a qualitative approach with a case study method, data was collected through in-depth interviews with employees, users, and HR involved in the selection process, supplemented by analysis of CV and portfolio documents. A well-structured CV attracts initial HR attention, while an informative, narrative portfolio provides concrete evidence of skills, especially for roles requiring visual proof of work. Both act as communication symbols reflecting an individual's values and competencies, with interview communication effectiveness influenced by adaptability and storytelling. This research provides insights for companies and HR to improve recruitment effectiveness and for applicants to optimize digital CV and portfolio integration, highlighting the importance of balancing professionalism with authenticity.